TATHWîR MÂDAH TA'LîM AL-BALÂGHAH Fî DHAU AL-KHARÂITH AL-DZIHNIYAH AL-ILIKTRÛNIYAH WA WASÂIL AL-TAWÂSHUL AL-IJTIMÂ'I - Ahmad Nurcholis (Arabi : Journal of Arabic Studies, 2018)
The researcher’s observation has shown that in many education institutions including those at higher education, Balaghah Instructional Material and its Strategies seem to be monotonous and traditional (based on Behaviorism theory), with which students tend to be passive in their teaching and learning activities. This research was then aimed at both developing model of teaching Balaghah using e-mind mapping and social media, and knowing the effectiveness of this teaching model towards the learning competence of students of Arabic Education Department of State Islamic Institute of Tulungagung. The design of this research was a modified model of Borg’s and Gall’s Research Development (RD) which consists of nine (9) stages. The finding of this research was developing Balaghah instructional material using e-mind map and social media which was focused on student-centered,  informative, explorative, implementative and cooperative activities, increased the students’ competence of learning Balaghah.